Prediction of fatigue life of geometrically deviated steam turbine blades under thermo-mechanical conditions - Mashiachidi, Makgwantsha Hermelton; Desai, Dawood A. (Frontiers in Manufacturing Technology, 2024)
This study explores the intricate factors affecting the fatigue life of steam turbine blades, encompassing steam flow-induced bending, centrifugal loading, vibration response, structural mistuning, and temperature-dependent influences. Focusing on the significance of mistuned steam turbine blades with varying blade geometries due to manufacturing tolerances, this research has paramount relevance for the power generation industries. Employing finite element analysis (FEA) software, a simplified, mistuned, scaled-down steam turbine bladed disk model was developed, considering temperature-dependent material properties. Initial FEA analyses provided insights into vibration characteristics and steady-state stress responses, with numerical stress distributions evaluated which were subsequently exported to Fe-Safe software for fatigue life calculations based on centrifugal and harmonic sinusoidal pressure loadings. By investigating the vibration characteristics and response to geometric blade variations, this study affirmed the reliability of the developed FEA model, with findings highlighting the pronounced sensitivity of fatigue life to blade length, width, and thickness variations, in this order. However, in order to validate the developed numerical models, analytical life cycle assessments were calculated which exhibited a discrepancy of under 3.37%, reinforcing the applicability of the developed numerical methodology to real-world scenarios involving mistuned steam turbine blades experiencing manufacturing deviations in blade geometry.